Transition Test Supplement - Bareiša, E.; Jusas, V.; Motiejūnas, K.; Šeinauskas, R. (Elektronika ir Elektrotechnika, 2006)
The design complexity of systems on a chip drives the need to reuse intellectual property cores, whose gate-level implementation details are unavailable. The core test depends on manufacturing technologies and changes permanently during a design lifecycle. The purpose of this paper is to assist the designer in the decision making how to test transition faults of re-synthesized intellectual property cores. The comparison of the detection of the transition faults for different implementations of the circuit was carried out. Our experiments show that the test sets generated for a particular circuit realization fail to detect in average only less than one and a half percent of the transition faults of the re-synthesized circuit but in some cases this figure is more than 7%. The possibility of reuse the functional delay test was studied, too. Ill.1, bibl. 22 (in English, summaries in English, Russian and Lithuanian).